Intra- and Interspecific Prey Theft in Cicada Killers (Hymenoptera: Apoidea: Sphecius). Issue 1 (6th February 2019) - Coelho, J R; Holliday, C W; Hastings, J M
Abstract: We studied prey theft in two cicada killer aggregations: Ruby, Arizona ( Sphecius convallis Patton) and Easton, Pennsylvania ( Sphecius speciosus Drury). Many prey ( Tibicen parallelus Davis [Hemiptera: Cicadidae]) were stolen from S. convallis by kingbirds and Greater Roadrunners at Ruby. Seventy percent of kingbird attacks on provisioning wasps were successful. Using sand-filled trap nests baited with a cicada, we tested the hypothesis that conspecific females might kleptoparasitize by laying an egg on the cicada and closing the nest cell. At Ruby, 45% were so appropriated, and at Easton, 52%. Easton data showed that the longer a nest cell was left open, the higher the rate of kleptoparasitism. Hence, intraspecific kleptoparasitism likely occurs at high rates in both populations. Not needing to dig a burrow, or to hunt, capture, and carry a paralyzed cicada favors intraspecific kleptoparasitism in cicada killers. Low cicada availability and intense avian kleptoparasitism of cicada killers may intensify selection pressure for this behavior at the Arizona site. Pirating cicadas may be the only viable reproductive outlet for females that are small or in environments with few prey. We suggest that provisioned nest cell kleptoparasitism may have evolved in cicada killers as an alternative strategy to standard provisioning, given the dual uncertainties of adult body size and prey availability.